PENGETAHUAN DAN MOTIVASI IBU TENTANG PENCEGAHAN DIARE PADA BALITA DI PUSKESMAS PUTRI AYU KOTA JAMBI TAHUN 2016 - Suharni Setia Ningsih; Tina Yuli Fatmawati (Jurnal Akademika Baiturrahim Jambi, 2017)
Background:The mortality rate of infants and toddlers in Indonesia is the highest in ASEAN countries. The cause of morbidity and mortality most children today are still caused by pneumonia and diarrhea. Diarrheal disease still is one of the major diseases in infants and children in Indonesia. It is estimated morbidity rate ranged between 150-430 per thousand population annually.Method:This research is a descriptive survey which aims to reveal the mother's knowledge and motivation about the prevention of diarrhea in infants at Puskesmas Putri Ayu 2016. This research was conducted in Puskesmas Putri Ayu Kota Jambi. The population of this research is the average number of monthly children who suffer from diarrhea in 2015 which is an average of 155 childrenand the number of samples in this research as much as 46 respondents. Sampling using accidental sampling technique. The data collectiondone by questionnaire. This research has been conducted on Juni-July 2016. The data analysis is univariateanalysis.Result:The results showed, 34 respondents (73.9%) had very good knowledge, 12 respondents (17%) had good knowledge and 5 respondents had enough knowledge. 32 respondents (91%) have a high motivation on the prevention of diarrhea in infants and low motivation 14 respondents(9%).In this research we can conclude that the knowledge and motivation of mothers on prevention of diarrhea high for the majority, it is advisable for it suggested health officials in order to keep giving information and education programs on the health care of infants and children expecially the prevention of diarrheain infants.